ANALYZING THE PICTURE OF EYL TEXTBOOK THROUGH MULTIMODAL DISCOURSE PERSPECTIVE - Fristiara, Cahyaning (LET: Linguistics, Literature and English Teaching Journal, 2017)
The aim of this research is to find out the value inside the picture of English textbook based on the characteristic of young learners. This research used qualitative research method. Data collected by analyzing an EYL textbooks and choosing one theme deserved with the aim of the research. Some pictures in chapter four of EYL textbook in Indonesia with the title Dinda Cooks in the Kitchen used as the data. Analyzing the data used descriptive analysis through multimodal discourse perspective related with systemic functional linguistic. The result shows that most of the aspect in the picture appropriates with characteristic of EYL and needs additional information and revision insight the design. Furthermore, the textbook developer should design the appropriate picture in transferring Indonesian culture. Transferring the culture assumed to maintain studentsâ interest, to evolve more meaningful picture, and to increase studentsâ ability in remembering the lesson based on the real context.